The Epidemiology of Microsporidias in Humans (Malatya sample) - Karaman, Uelkue; Daldal, Nilguen; Atambay, Metin; Colak, Cemil (Tubitak Scientific & Technological Research Council Turkey, 2009)
Aim: Microsporidias, first isolated and defined in 1857, are obligate intracellular parasites observed in animal groups and especially invertebrates. Generally homosexual patients and patients who are HIV positive and immune suppressed constitute the participants of international studies about the epidemiology of microsporidias. No previous studies about the prevalence of the parasite in Turkey have been found in the literature. This study aimed to determine the epidemiology of microsporidias in and around Malatya. Materials and Methods: Feces samples (n: 2665) from patients who presented at inonu University Medical Faculty policlinics in 2006 with some digestive system complaints and were referred to the Parasitology Department were analyzed. The samples were analyzed using modified trichrome (MTS). Acid-Fast-Trichrome, Calcofluor, and Giemsa staining. Results: In all 226 samples (8.5%) were positive. There was a statistically significant relationship between lack of appetite, general body pruritus. immune suppression + cancer. dyspnea, and ulcerative colitis. Conclusions: It is important to check feces samples for Microsporidium spp. parasites regularly for cases including unexplained diarrhea, stomachache, lack of appetite, general pruritus, immune suppression + cancer, asthma, and ulcerative colitis, since Microsporidium spp. is not a commonly known parasite in Turkey.
Keywords: Microsporidium spp.; Malatya; epidemiology; Turkey